Democratic Republic of Timor-Leste : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper provides an overview of past growth performance and an assessment of the outlook for growth in Timor-Leste. It identifies impediments to growth and discusses policies that would contribute to the accelerated rates of growth needed to reduce poverty and unemployment and the other objectives of the National Development Plan. The paper reviews the macroeconomic challenges commonly faced by oil/gas exporters. It discusses Timor-Leste's oil/gas revenue outlook, and plans for managing the oil/gas wealth through a natural resource (petroleum) fund and a saving policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet